2020
DOI: 10.1186/s40594-020-00251-2
|View full text |Cite
|
Sign up to set email alerts
|

Transforming education with community-developed teaching materials: evidence from direct observations of STEM college classrooms

Abstract: Background The Classroom Observation Project employs direct observations of geoscience teaching across the USA using the Reformed Teaching Observation Protocol (RTOP) to quantify the use of reformed teaching practices. We report on 345 RTOP observations used to evaluate the extent of teaching reform when curricular materials developed as part of the InTeGrate Project (ITG) were used. The InTeGrate Project has published 40 modules of curricular materials that teach geoscience in the context of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…(Radziwill, Benton & Moellers, 2015) found that in comparison with STEM-only he recognized that project centered with STEAM could enhance learner's perspective to work creatively. STEAM field can be brought to solve problems, design system, and live a more earth-friendly lifestyle (Teasdale, Ryker, Viskupic, Czajka & Manduca, 2020). The advantages of STEAM education varied from, developing learners' self-directed learning potential, cultivating the appropriate character, and enhancing students' academic outcomes (Lee, 2021).…”
Section: Theoretical Analysismentioning
confidence: 99%
“…(Radziwill, Benton & Moellers, 2015) found that in comparison with STEM-only he recognized that project centered with STEAM could enhance learner's perspective to work creatively. STEAM field can be brought to solve problems, design system, and live a more earth-friendly lifestyle (Teasdale, Ryker, Viskupic, Czajka & Manduca, 2020). The advantages of STEAM education varied from, developing learners' self-directed learning potential, cultivating the appropriate character, and enhancing students' academic outcomes (Lee, 2021).…”
Section: Theoretical Analysismentioning
confidence: 99%
“…The word discipline comes from Latin; discipline means exercise or education (Wilson, 2010). From forming discipline derived from the verb discere, meaning teaching, then disciplinary means teaching, educating and expanding Cubero et al, 2020;Deane, 2020;Guan et al, 2020;Hong & Basturkmen, 2020;Teasdale et al, 2020).…”
Section: Disciplinementioning
confidence: 99%
“…Teaching materials that can be used include textbooks, modules, handouts and worksheets. The use of teaching materials can make learning more meaningful (Teasdale et al, 2020;Theil et al, 2021). Teaching materials help students so that they are no longer fixated on the teacher's explanation.…”
Section: Introductionmentioning
confidence: 99%